2021
DOI: 10.1136/jim-2021-001871
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors, symptoms, and outcomes of North American patients with autoimmune hepatitis during the COVID-19 pandemic

Abstract: The management of patients with autoimmune hepatitis (AIH) in the era of SARS-CoV-2 is challenging given minimal published clinical data. We used a large cohort of patients with AIH across the USA to investigate the differences in known risk factors for severe SARS-CoV-2 and AIH characteristics among patients who experienced symptoms consistent with COVID-19 illness versus those who did not. Additionally, we explored the effect of living through the SARS-CoV-2 pandemic on the extrahepatic symptoms and behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“… 30 (52%) patients with AIH were on combined immunosuppression with ≥2 agents. VahinVuppalanchi et al [31] N=420 AIH:420 Liver biopsy reported cirrhosis:78 Immune suppressants for the AIH treatment do not increase the risk of severe COVID-19. / / Alessio Gerussi et al [32] N=10 AIH patients:10 Cirrhosis: 4 Decompensated cirrhosis (Child-Pugh B): 6 / 9 patients are still alive and asymptomatic, and 1 (patient 6) died.…”
Section: Impact Of Covid-19 On Patients With Pre-existing Chronic Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation
“… 30 (52%) patients with AIH were on combined immunosuppression with ≥2 agents. VahinVuppalanchi et al [31] N=420 AIH:420 Liver biopsy reported cirrhosis:78 Immune suppressants for the AIH treatment do not increase the risk of severe COVID-19. / / Alessio Gerussi et al [32] N=10 AIH patients:10 Cirrhosis: 4 Decompensated cirrhosis (Child-Pugh B): 6 / 9 patients are still alive and asymptomatic, and 1 (patient 6) died.…”
Section: Impact Of Covid-19 On Patients With Pre-existing Chronic Liver Diseasementioning
confidence: 99%
“…The immune function of autoimmune hepatitis (AIH) patients is passively suppressed, and their liver may be decompensated at the same time, which may have adverse effects on the recovery of COVID-19. Several large multicenter studies have found that COVID-19 patients seemed to have a similar disease process as the general patients among the patients who received immunosuppressive therapy, and immunosuppression may also reduce the risk of new-onset liver injury [29] , [30] , [31] . Reducing immunosuppression in AIH (applicable to other autoimmune diseases) patients during the pandemic may be detrimental, as it may expose individuals to a higher risk of disease recurrence.…”
Section: Impact Of Covid-19 On Patients With Pre-existing Chronic Liver Diseasementioning
confidence: 99%
“… 15 In addition, a survey of patients with autoimmune hepatitis who are also vulnerable to infection and severe complications due to a suppressed immune system found that a majority of patients would make changes to their behavior like limiting entertainment outside the home, mask wearing, and limiting interactions with family and friends after the strict stay-at-home orders were relaxed. 11 However, these surveys were completed before vaccinations were available.…”
Section: Introductionmentioning
confidence: 99%
“…10 In a study of patients with autoimmune hepatitis, the authors found that patients with COVID-19 symptoms reported increased fatigue, anxiety, and itch compared with those without symptoms of COVID-19. 11 Furthermore, frequent contacts with the health care system lead to a higher risk of infection. 12 Masks along with social distancing are effective non-pharmaceutical public health interventions to reduce the rate of infection.…”
mentioning
confidence: 99%
“…Наиболее уязвимыми для вируса SARS-CoV-2 (группы риска) являлись пациенты с циррозом печени (особенно декомпенсированным), с прогрессирующими хроническими диффузными заболеваниями печени, с аутоиммунными заболеваниями печени (особенно получающие иммуносупрессивную терапию), после трансплантации печени, с гепатоцеллюлярной карциномой, с неалкогольной жировой болезнью печени [6][7][8]. Хотя первичные клинические проявления связаны с поражением легких, в настоящее время признано, что COVID-19 является системным заболеванием, связанным с непредсказуемым иммунным ответом организма человека, приводящим к активации свертывающей системы крови, полиорганной недостаточности и смерти [9][10][11]. Известно, что у пациентов с сопутствующим хроническим паренхиматозным заболеванием печени, в частности декомпенсированным циррозом печени, инфекция COVID-19 может быть ассоциирована с более высоким риском летального исхода [12][13][14][15][16] -летальность достигает более 30 % [8].…”
unclassified